Probing Protein-protein Interactions and Druggable Site Identification: Mechanistic Binding Events Between Ubiquitin and Zinc Finger with UFM1-specific Peptidase Domain Protein (ZUFSP) - Ajadi, Mary B.; Soremekun, Opeyemi S.; Elrashedy, Ahmed A; Olotu, Fisayo A.; Kumalo, Hezekiel M.; Soliman, Mahmoud E.S. (Combinatorial Chemistry & High Throughput Screening, 2022)
Background: Deubiquitinating enzymes (DUBs) protein family have been implicated in some deregulated pathways involved in carcinogeneses, such as cell cycle, gene expression, and DNA damage response (DDR). Zinc finger with UFM1-specific peptidase domain protein (ZUFSP) is one of the recently discovered members of the DUBs. Objectives: To identify and cross-validate the ZUFSP binding site using the bioinformatic tools, including SiteMap&Metapocket, respectively. To understand the molecular basis of complementary ZUFSP-Ub interaction and associated structural events using MD Simulation. Methods: In this study, four binding pockets were predicted, characterized, and cross-validated based on physiochemical features such as site score, druggability score, site volume, and site size. Also, a molecular dynamics simulation technique was employed to determine the impact of ubiquitin-binding on ZUFSP. Results: Site 1 with a site score 1.065, Size 102, D scores 1.00, and size volume 261 was predicted to be the most druggable site. Structural studies revealed that upon ubiquitin-binding, the motional movement of ZUFSP was reduced when compared to the unbound ZUFSP. Also, the ZUFSP helical arm (ZHA) domain orient in such a way that it moves closer to the Ub; this orientation enables the formation of a UBD which is very peculiar to ZUFSP. Conclusion: The impact of ubiquitin on ZUFSP movement and the characterization of its predicted druggable site can be targeted in the development of therapeutics.
Keywords: deubiquitinating enzymes